Recombinant Protein Expression System in Corynebacterium glutamicum and Its Application - Lee, Min Ju; Kim, Pil (Frontiers in Microbiology, 2018)
Corynebacterium glutamicum, a soil-derived Gram-positive actinobacterium, has been widely used for the productions of biochemical molecules such as amino acids (i.e., L-glutamate and L-lysine), nucleic acids, alcohols, and organic acids. The metabolism of the bacterium has been engineered to increase the production of the target biochemical molecule, which requires cytosolic enzyme expression. As recent demand for new proteinaceous biologics (such as antibodies, growth factors, and hormones) increases, C. glutamicum is attracting another industrial interest as a recombinant protein expression host for therapeutic protein production due to advantages such as low protease activity without endotoxin activity. In this review, the recent studies on the heterologous expression of the recombinant protein in C. glutamicum for metabolic engineering, expansion of substrate availability, and recombinant protein secretion are summarized. Advances in genetic components such as promoters, surface anchoring systems, and secretory signal sequences in C. glutamicum for effective recombinant protein expression are also summarized.